BIMBINGAN KONSELING ISLAM DENGAN TERAPI BEHAVIOR UNTUK MENANGANI ADIKSI MEROKOK PELAJAR SD - Khotimah, khusnul; Syakur, Abd (Jurnal Bimbingan dan Konseling Islam, 2022)
The focus of this study were (1) How is the Islamic Guidance and Counseling with Behavior Therapy in dealing with the addiction of smoking an elementary school in the village of Pangkahkulon Ujungpangkah Gresik ?; and (2) How do the results of guidance and counseling Islam with Behavior Therapy in dealing with the addiction of smoking an elementary school in the village of Pangkahkulon Ujungpangkah Gresik ?. This study uses descriptive qualitative comparative analysis. The analysis is based on interviews and observations. This research was conducted through behavior therapy with modeling techniques. Mechanical modeling is done by using symbolic models and real models. Modeling techniques performed while observation by adding and subtracting the observed behavior. The purpose of this therapy is to eliminate poor behavior towards better. Haasil the end of the process of counseling to clients in this study was quite successful with a percentage of 75%. These results can be seen from the change in clients who had not smoked again and changes in behavior on the client's self after receiving guidance and counseling provided by counselors Islam.